The relationship between emotional regulation, peer support and aggressive behaviour among undergraduate students in Malaysia - Ong, Yee Chiun (2023)
This quantitative research aims to examine the relationship between emotional regulation, peer support, and aggressive behaviour among undergraduate students in Malaysia. A crosssectional study was conducted among 212 participants recruited through the use of the purposive sample approach for a cross-sectional study. In all, 212 college students participated in the study; their ages (M = 21.22, SD = 2.934) ranged from 17 to 26 years old. The study employs standardised instruments to measure emotional regulation strategies, assess perceived levels of peer support, and quantify instances of aggressive behaviour. The instruments used were the Emotion Regulation Questionnaire (ERQ), the Peer Support Questionnaire (PSQ), and the Aggression Questionnaire (AGQ). The degree and direction of the relationships between these variables will be investigated using the statistical technique of Pearson product-moment correlation. Subgroup analyses will also be carried out to investigate any moderating effects that might arise from contextual or demographic factors. The results demonstrate that among undergraduates, there is a substantial correlation between peer support and emotional regulation. Nonetheless, there is no relationship between emotional regulation and aggressive behaviour, and the null hypothesis is rejected between peer support and aggressive behaviour. The result of this study provides practical insights for university students, counsellors, and educators in Malaysia on coping mechanisms for emotional regulation by considering peer support and reducing aggression.